FAILED INDUCTION OF LABOR AND ASSOCIATED RISK FACTORS AMONG WOMEN UNDERGOING INDUCTION - ASHIQ , F; SARWAR , S; FAIZ , A; KHALID , L; ASLAM , S; FAROOQ , N (Biological and Clinical Sciences Research Journal, 2024)
Induction of labor is a standard obstetric procedure aimed at initiating uterine contractions before the spontaneous onset of labor. While it is a critical intervention to prevent maternal and fetal complications, failed induction remains a significant challenge, often leading to cesarean deliveries and adverse maternal outcomes. Identifying the frequency and associated risk factors for failed induction is crucial for optimizing perinatal care and improving maternal and fetal outcomes. Objective: To determine the frequency of failed inductions of labor and identify the associated risk factors in pregnant women undergoing induction at a tertiary care public hospital in Islamabad. Methods: A cross-sectional study was conducted at the Gynecology & Obstetrics Department, Federal Government Poly Clinic Hospital, Islamabad, from May 16, 2023, to November 15, 2023. One hundred ninety-six pregnant women undergoing induction of labor were included in the study. Patients were followed up until delivery to assess the success or failure of induction, and the reasons for failed induction were recorded. Data were analyzed using the **Statistical Package for Social Sciences (SPSS) version 16**, with results presented as mean ± standard deviation (SD) and frequencies. Results: The mean age of participants was 27.2 ± 4.7 years, with an age range of 18–40 years. The overall success rate of induction of labor was 72.4% (n = 142), while 27.6% (n = 54) of inductions failed. The most common risk factor for failed induction was a low Bishop score, observed in **17.9% (n = 35) of cases, followed by pre-eclampsia, present in 15.8% (n = 31) of cases. Conclusion: Failed induction of labor remains a prevalent issue, with low Bishop score and pre-eclampsia emerging as the most significant risk factors. Early identification and management of these factors may improve induction outcomes and reduce maternal and fetal complications. Further research is warranted to develop targeted interventions for optimizing labor induction success rates.